2021
DOI: 10.3389/fped.2021.624798
|View full text |Cite
|
Sign up to set email alerts
|

Association Between rs12037447, rs146732504, rs151078858, rs55723436, and rs6094136 Polymorphisms and Kawasaki Disease in the Population of Polish Children

Abstract: Background: Kawasaki disease (KD) is an acute self-limited febrile vasculitis that mainly affects young children. Coronary artery involvement is the most serious complication in children with KD. It is currently the leading cause of acquired cardiac disease in children from developed countries. Literature data indicate a significant role of genetic susceptibility to KD.Objective: The aim of this study was to perform the first Genome-Wide Association Study (GWAS) in a population of Polish children with KD and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…It is worth emphasizing that all patients came from Poland (particularly the Masovian Voivodeship), and there were no ethnic differences (homogeneous Caucasian population). Our genetic studies revealed that polymorphisms of genes KIF25, PTRPJ, SPECC1L, and RNP2 might be linked with KD incidence in Polish children [23].…”
Section: Discussionmentioning
confidence: 78%
“…It is worth emphasizing that all patients came from Poland (particularly the Masovian Voivodeship), and there were no ethnic differences (homogeneous Caucasian population). Our genetic studies revealed that polymorphisms of genes KIF25, PTRPJ, SPECC1L, and RNP2 might be linked with KD incidence in Polish children [23].…”
Section: Discussionmentioning
confidence: 78%
“…[ 1 ] A recent study by Buda et al . [ 16 ] showed that polymorphisms of genes KIF25 , SPECC1L and RNP2 may also have influence on susceptibility to KD.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki disease is an acute self-limited febrile vasculitis, mainly affecting young children and believed to be the product of a genetic susceptibility to incorrectly activate the immune system and an environmental trigger. Given CD148’s involvement in vasculogenesis and being also expressed in hematopoietic cells, in hindsight it seems logical that in a micro-array genotyping study (involving 164,395 SNPs, 119 Polish patients and over 6K controls) the polymorphism rs151078858 in PTPRJ was among the five that were most statistically linked with Kawasaki disease ( Buda et al, 2021 ). Moreover, two protein-truncating PTPRJ alleles (p.T38Pfs9* and p.S626Afs7*) have recently been discovered in a study towards genes underlying inherited thrombocytopenia and, importantly, functional studies in zebrafish and mouse models underscored the important role for PTPRJ in platelet biogenesis ( Senis et al, 2009 ; Marconi et al, 2019 ; Nagy et al, 2020 ).…”
Section: Documented Genetic Variabilitymentioning
confidence: 99%